Tuning the Optical Depolarization and Absorption in Freestanding Zno Nanorod/Nanotube Arrays Decorated with Sns Nanoparticles Through Control of the Synthesis Parameters - Valdivia-Lefort, P (Elsevier Ltd, 2025)
The combination of ZnO nanotubes and SnS nanoparticles in core-shell nanoarchitectures has potential advantages for photoelectrochemical applications due to increased absorption, optimized band alignment, improved stability and large surface to volume ratios. The fabrication of these structures usually involves a three-step process, limiting their application when high throughput is required. This work presents a synthesis method based on SILAR deposition, a low cost technique, that successfully deposits the nanoparticles while simultaneously forming nanotubes, reducing the number of synthesis steps to two. In order to evaluate the resulting nanostructures for photoelectrochemical applications, morphological and optical characterizations of the resulting nanorod and nanotube arrays are performed. The absorption spectra of each sample is reconstructed through the Tauc plot method, with the samples showing both a direct and an indirect bandgap of SnS. It is shown that the formation of nanotubes affects the strain in the SnS shell, modifying the Urbach tail by generating mid-gaps states, which has potential as a control parameter to tailor optical performance. Lastly, the polarization properties of the 1D nanostructures associated with their elongated morphology are explored, which showed a clear relationship between underlying nanorod and nanotube morphology, the scattering properties and the polarization state of light. © 2025 Elsevier B.V.